2008
DOI: 10.1183/09031936.00021008
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial fistulae in ARDS patients: management with an extracorporeal lung assist device

Abstract: Patients with bronchial tree lesions feature, in particular, a high risk for developing bronchial fistulae after surgical repair when the clinical situation is complicated by acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) and mechanical ventilation is needed. The current authors hypothesised that extracorporeal carbon dioxide removal would significantly decrease inspiratory airway pressures, thus promoting the protection of surgical bronchial reconstruction.Four patients were studied after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 18 publications
0
13
0
3
Order By: Relevance
“…In all four patients, the use of pECLA corrected hypercapnia and enabled the reduction of airway pressures, and all patients were eventually discharged from the hospital. As HOMMEL et al [12] point out in their paper, there is no proof that the use of pECLA was responsible for the good outcome but there are compelling pathophysiological reasons supporting this hypothesis.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…In all four patients, the use of pECLA corrected hypercapnia and enabled the reduction of airway pressures, and all patients were eventually discharged from the hospital. As HOMMEL et al [12] point out in their paper, there is no proof that the use of pECLA was responsible for the good outcome but there are compelling pathophysiological reasons supporting this hypothesis.…”
mentioning
confidence: 90%
“…In the present issue of the European Respiratory Journal, HOMMEL et al [12] report on four patients with ARDS and bronchopleural fistulas with persistent air leakage despite surgical interventions. These patients usually have a poor prognosis if they develop respiratory failure and require mechanical ventilation with high airway pressures.…”
mentioning
confidence: 99%
“…Overall, there is good evidence that ECCO 2 R can effectively reduce PaCO 2 and make a small contribution to oxygenation in patients with ARDS. Likewise, studies 14,[18][19][20]22,23 have demonstrated that ECCO 2 R facilitates a lung-protective ventilation strategy by allowing a reduction in tidal volumes and inspiratory airway pressures. ECCO 2 R may even complement specific forms of protective ventilation such as HFOV 21,24 or APRV (Airway Pressure Release Ventilation) with 2-4 mL/kg tidal volumes.…”
Section: Current Evidencementioning
confidence: 99%
“…There are a number of reports of its use in other clinical scenarios, namely, as a bridge to transplant, 11,25 in combined head and chest injury, 7,8,26 in near fatal asthma, [27][28][29] as an aid to weaning from mechanical ventilation, 12,30 to facilitate thoracic surgery 19,22,31 and to facilitate transfer. 32,33 However, these are all case reports or very small case series and as such do not provide any definitive evidence of benefit.…”
Section: Current Evidencementioning
confidence: 99%
See 1 more Smart Citation